VARIASI KEGIATAN LITERASI DI TBM BINA CENDEKIA TAMPO DI KABUPATEN MUNA, SULAWESI TENGGARA - Rasiah Rasiah; La Bilu Bilu; Ela Martisa (Seshiski: Southeast Journal of Language and Literary Studies, 2022)
This article intended to show the literacy program which aims to develop Community Reading Parks (TBM) as an effort to improve literacy activities in rural areas. The object is TBM Bina Cendekia, located in Tampo, Napabalano District, Muna Regency, Southeast Sulawesi. TBM Bina Cendekia Tampo is one of the literacy activity places in rural areas that was voluntarily established in 2011 and received an operational permit in 2016. However, its management and literacy services are still very limited. The problem faced by management team is the lack of community motivation to visit the TBM that made to TBM is like suspended. The solutions offered in this partnership activity are, one of them, socializing a variety of literacy activities that are entertainment-oriented and educational. Reading activities remain the focus of activities by presenting an atmosphere of "mobile stalls". Other activities that can be carried out are activities to grow interests and talents, discussions, and competitions or exhibitions.